Critical theory of the energy transformation: Sociology’s approach - Baranowski, Mariusz (Society Register, 2023)
This article explores the critical theory of energy transformation within sociology, aiming to understand and enhance societal change. It investigates the shift from fossil fuels to renewable energy sources, analysing the socio-economic and geopolitical implications. Using empirical data, it reveals disparities between public discourse and actual emissions, unmasking power asymmetries and ‘green colonialism’ perpetuated by dominant nations and corporations. The study underscores the need for profound societal transformation rather than superficial energy shifts, advocating for the fusion of critical theory and capitalist critiques. It emphasises the importance of dismantling hegemonic control and fostering equitable energy transformation, calling for civic courage to challenge existing power structures. This work’s originality lies in integrating critical theory within sociology, offering insights into the socio-political dynamics influencing global decarbonisation efforts. Its value resides in a comprehensive analysis, unveiling interconnections between power, economics, and the environment in the context of energy transformation.